KESENYAPAN NARASI KOLONIALISME DALAM NOVEL-NOVEL SUNDA RENTANG 1914—1940: WACANA MENGINGAT DAN MELUPAKAN (The Silent of Colonialism Narratives in Sundanese Novels Circa 1914—1940: Memory Discourse about Remembering and Forgetting) - Hudayat, Asep Yusup; Rahayu, Lina Meilinawati; Muhtadin, Teddi A.N. (Kandai, 2023)
In the early 20th century circa 1914–1940 were Sundanese novels almost "silent" from the colonialism narratives. This condition shows that memories were forgotten, suppressed, ignored, or even omitted in literary works because of the domination of the Dutch East Indies. However, the colonial traces can be revealed through how the narratives are constructed and presented. Through their works, the authors (from the middle class and educated) told about social reality and themselves in the challenges of social change in the early 20th century. This paper aims to reveal the memory selection process of Sundanese novelists in the early 20th century in producing their works under the dominant forces influences: feudal and colonial. The data analysis techniques were as follows, (a) data instrumens: narrative tools, special expressions, projection, and contruction (b) describing the data instrumens, (c) interpreting the data, (d) conclusions. The analysis results are: (1) the authors positioning (as teachers, natives, and employees of the Balai Pustaka) had an affects on the memories selections that were used to constructing narratives about domination and power, (2) the narratives of colonialism memories in five novels are built in three ways: suppressed, diverted, and even erased, (3) The voices behind the colonialism-narratives silent are expressed through the metaphorical traces of power, the pre-colonial and colonial memories as background, and indigenous marginal discourse. Pada awal abad ke-20 sekitar tahun 1914—1940 novel-novel Sunda nyaris “diam” dari narasi kolonialisme. Kondisi ini menunjukkan bahwa ingatan dilupakan, ditekan, diabaikan, atau bahkan dihilangkan dalam karya sastra karena dominasi Hindia Belanda. Namun, jejak kolonial dapat terungkap melalui bagaimana narasi dibangun dan disajikan. Melalui karya-karyanya, para pengarang (dari kelas menengah dan terpelajar) bercerita tentang realitas sosial dan diri mereka sendiri dalam tantangan perubahan sosial di awal abad ke-20. Tulisan ini bertujuan untuk mengungkap proses seleksi ingatan para novelis Sunda di awal abad 20 dalam menghasilkan karya-karyanya di bawah pengaruh kekuatan dominan: feodal dan kolonial. Teknik analisis data adalah sebagai berikut, (a) instrumen data: alat naratif, ungkapan khusus, proyeksi, dan konstruksi (b) mendeskripsikan instrumen data, (c) menafsirkan data, (d) kesimpulan. Hasil analisis adalah: (1) positioning pengarang (sebagai guru, pribumi, dan pegawai Balai Pustaka) berpengaruh terhadap pemilihan memori yang digunakan untuk mengkonstruksi narasi tentang dominasi dan kekuasaan, (2) narasi memori kolonialisme dalam lima novel dibangun melalui tiga cara: ditekan, dialihkan, dan bahkan dihapus, (3) suara-suara di balik narasi-narasi kolonialisme diekspresikan melalui jejak metaforis kekuasaan, kenangan pra-kolonial dan kolonial sebagai latar, dan marginalisasi pribumi.